A Comparative Analysis of Botswana’s Development Experience with Namibia and Gambia(1996-2009) - Bih Azefor, HILDA (The Graduate School, Ajou University, 2011)
At independence in 1966, Botswana was one of the poorest countries on earth with per capita income of about $70. Less than five decades after independence, Botswana has rapidly transformed itself from a traditionally subsistent economy into one of the finest development success models in the world, with per capita income of $13,900 as of 2008. Behind this impressive track record lies a possible web of causes. This research seeks to examine the contribution of political development within the country, in the context of governance capacities. It is submitted that worldwide governance indicators encapsulate the level of institutional progress that arguably sheds light on Botswana’s economic growth over time. A comparative examination of countries like Namibia and Gambia reveals that like most African countries, a focus on the development of governance capacities through institutional building matters in national development. But in spite of Botswana’s impressive governance system and economic growth rate over time, the country profusely suffers from human development issues such as the HIV pandemic, low life expectancy, high infant mortality and even staggering literacy rates. It follows therefore that although the Botswana has achieved unsurpassed economic growth rates, economic development for the country still remains wishful thinking.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2011. 2
Keywords: Botswana’s Development Experience